ANALISIS REKSADANA SYARIAH DALAM KONSEP NILAI AKTIVA BERSIH (NAB) - Tania, Atika Lusi (Institut Agama Islam Bengkulu, 2016)
Mutual fund composed of two concepts, namely mutual meaning keep or keep and the concept of the Fund means the set of money. Mutual funds means a collection of money is kept. Mutual funds (mutual fund) is a vehicle used to gather a Community Fund (financiers) to then be invested into the portfolio effect by investment managers (MI). The effect can be a portfolio of stocks, bonds, money market instruments, or a combination of some of these capital market law No. 8 year 1995 article 1, paragraph (27):